A novel and large area suitable water-based ink for the deposition of cobalt sulfide films for solar energy conversion with iodine-free electrolytes. (December 2015) - Congiu, Mirko; Lanuti, Alessandro; di Carlo, Aldo; Graeff, Carlos F.O.
Graphical abstract: Highlights: We proposed a low-cost CoS precursor ink suitable for large area deposition. The method does not use the toxic thiourea nor organic solvents. High efficiency CoS counter electrodes in DSSC with iodine-based electrolyte. High catalytic efficiency with polysulfide, ferrocene and cobalt-based electrolytes. Abstract: A novel, cheap, reliable water based precursor ink has been used for the large scale production of amorphous cobalt sulfide (CoS) on fluorine doped tin oxide (FTO). The method uses a metal–organic complex of Co(II) and thioglycolic acid (TGA), it is cheap and easy to prepare. The electrodes prepared using our method have been applied in the oxidation/reduction using different redox couples dissolved in liquid electrolytes containing: I − /I3 − ; ferrocene/ferrocenium; bipyridine [Co(bpy)3 ] 2+/3+ complexes and sodium polysulfide. The composition, morphology and the efficiency of the CoS electrodes have been investigated. The CoS films show a good adherence to the substrate, good transparency and an excellent electrocatalytic efficiency with all of the different redox electrolytes. The electrodes have been used in DSSC devices using the organic dye D5 with efficiencies up to 6.8%.